Seismic performance evaluation of a proposed buckling-restrained brace for RC-MRFS - Ebanesar, Arunraj; Cruze, Daniel; Noroozinejad Farsangi, Ehsan; Seenivasan, Vinscent Sam Jebadurai; Mohammad Adil, Dar; Abdul Rashid, Dar; Gladston, Hemalatha (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper presents a novel buckling-restrained brace (BRB) where the inner core is restrained by a concrete infilled Expanded Polystyrene Sheet (EPS) instead of the conventional concrete infilled tube section, to resist inner core buckling. It serves two purposes, firstly, the EPS is a ductile material, which is favourable in terms of seismic performance and, secondly, the outer construction material has better corrosion resistance.
Keywords: disasters seismic; disasters mitigation; buckling restrained brace; EPS; local buckling; local test; RC frame; OpenSees; katastrofy sejsmiczne; skutki katastrof; stabilizator zwalniający; wyboczenie; test obciążenia; Rama RC